PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA - Jaya Sutisna, Ade; Rohmatulloh, Puri; Sutarsih, Cicih (Universitas La Tansa Mashiro, 2023)
The purpose of this research is to determine the influence of school principal leadership, work motivation and compensation on performance. The quality of educational output cannot be separated from the relationship between supporting factors, seen from the average achievement of the Vocational School Teacher Competency Test (UKG) results in the Bina 1 Region of Lebak Regency which is still below the 2015 UKG Minimum Achievement Criteria (KCM) of 5.5 or in the range figure 5.2. The method used in this research is a survey with correlational techniques. The target population in this research is all State Vocational School teachers in the bina 1 area of Lebak Regency, totaling 265 people. Considering that the number of members of the target population is not too large, the reachable population in this case is the same as the target population. The number of samples used in this research was 82 teachers taken randomly. Partially or jointly, there is a significant influence on the independent variables of principal leadership (X1), work motivation (X2) and compensation (X3) on the dependent variable on the performance of State Vocational School teachers in Lebak Regency (Y).